BODY COMPOSITION AND CONDITIONAL CAPACITIES (Fiep Bulletin - online, 2013)
The purpose of this investigation is expressed by its title: Corporal composition and conditional capacity  in  high school children  in public schools in the city of Armenia, we focus on the quantitive-explanation, in a descriptive,  study  correlacional  and transversal.  Court in the population of 23.212 students, we evaluated a representative survey of 1.150, with a level  of 95% estimated error of 3%. We used functional test  for the conditional  training and the protocol of the international  Society for the Advancement of Kinanthropometry(ISAK). Following we digited the information in excel XP2007 were we calculated an average, deviation standard (DS) and correlation. The results show that in the average was of (48,66 kg) in the men of (49,35kg) and in the women (47,98 kg). For the  size was  of (170 cm), for the men (158cm) and the women (153cm). In the case of the physical training for the flexibility  the average was (2,26cm) for the men (1,34cm) and women (3,09cm); in the strength the average was of (149,68cm) in the women (129,26cm) and  the men (173,14cm); in the aceleration the average  was of (4,70sg) in men (4,53sg)  and the women (4,85sg) and the resistant variety  the data was (41,59Vo2) the men  (45,65Vo2) and the woman (38,05Vo2). it is concluded  that the aerobic capacity, the strength and the flexibility in the objective population, present low development in comparison with  the national and international index.
Keywords: Corporal composition; physical capacity conditional and schools